The double empathy problem, camouflage, and the value of expertise from experience. (2019) - Mitchell, Peter; Cassidy, Sarah; Sheppard, Elizabeth
Abstract: To understand why autistic people are misperceived in the way Jaswal & Akhtar suggest, we should embrace concepts like the "double empathy problem" and camouflaging and recognize the negative consequences these have for mental health in autism. Moreover, we need to value expertise from experience so that autistic people have a voice and indeed a stake in research into autism.